2016
DOI: 10.1016/j.rmed.2015.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Understanding asthma-chronic obstructive pulmonary disease overlap syndrome

Abstract: Asthma-chronic obstructive pulmonary disease overlap syndrome (ACOS) is a loosely-defined clinical entity referring to patients who exhibit characteristics of both asthma and chronic obstructive pulmonary disease (COPD). Clinical definitions and classifications for ACOS vary widely, which impacts our understanding of prevalence, diagnosis and treatment of the condition. This literature review was therefore conducted to characterize the prevalence of ACOS and the effect of different disease definitions on these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
54
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(61 citation statements)
references
References 42 publications
(58 reference statements)
4
54
0
3
Order By: Relevance
“…The findings of the present study are consistent with those reported in some general and selected COPD populations that have used the previous diagnosis of asthma plus spirometric COPD to define ACOS [3, 5, 7, 30]. The comparison with the PLATINO study deserves special consideration as this is another study from Latin America that use the same two ACOS definitions in the same population [3].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The findings of the present study are consistent with those reported in some general and selected COPD populations that have used the previous diagnosis of asthma plus spirometric COPD to define ACOS [3, 5, 7, 30]. The comparison with the PLATINO study deserves special consideration as this is another study from Latin America that use the same two ACOS definitions in the same population [3].…”
Section: Discussionsupporting
confidence: 88%
“…The prevalence of ACOS in the total population ranges from 1.6 to 4.5% in different studies around the world [15]. If only subjects with asthma or COPD are included, the prevalence of ACOS among patients with COPD ranges from 12.1 to 55.2%, and among patients with asthma from 13.3 to 61.0% [119].…”
Section: Introductionmentioning
confidence: 99%
“…Without such a case definition, it is impossible to collect (let alone interpret) data on its epidemiology, clinical course or therapeutic responsiveness. This lack of consensus, for instance, may explain the widely divergent data on the prevalence of ACOS, which ranges between 11% to 56% among patients previously diagnosed with COPD [35], 13% to 61% among patients previously diagnosed with asthma [76] and ∼2% in the general population over 40 years of age [77]. It may also explain why in some studies, ACOS has been associated with more female patients [78,79], while in others with more male patients [30,80].…”
Section: Recommendations On a Case Definition Of Acosmentioning
confidence: 99%
“…The proportions of ACOS patients among COPD patients in real-life clinical settings have been estimated in several reports previously 3. However, the designs and sampling methods of these studies have varied, and the prevalence values have ranged from 12% to 55%, mainly because of the difference between the definitions of ACOS followed in each study, including airflow reversibility, spirometry, and clinical diagnosis 3.…”
Section: Introductionmentioning
confidence: 99%
“…However, the designs and sampling methods of these studies have varied, and the prevalence values have ranged from 12% to 55%, mainly because of the difference between the definitions of ACOS followed in each study, including airflow reversibility, spirometry, and clinical diagnosis 3. Such discrepancies in the definition of ACOS have complicated our understanding of the epidemiology and clinical characteristics of this disease in terms of the symptoms, frequency and severity of exacerbations, and disease burden.…”
Section: Introductionmentioning
confidence: 99%